Cold feet - Larry G. Epstein; Igor Kopylov (Theoretical Economics, 2007)
Individuals often lose confidence in their prospects as they approach the `moment of truth.' An axiomatic model of such individuals is provided. The model adapts and extends (by relaxing the Independence axiom) Gul and Pesendorfer's model of temptation and self-control to capture an individual who changes her beliefs so as to become more pessimistic as payoff time approaches. In a variation of the model, the individual becomes more optimistic at an ex post stage in order to feel better about her available options.
Keywords: D80; D81; 330; Pessimism; optimism; cold feet; temptation; self-control; moment of truth; temporal proximity; confidence